The Bible literature in the beginning was the world - The Center for Humanties ([Mount Kisko, N.Y.] The Center, 1960)
The bible is the most influential work in Western civilization. Its words and ideas echo through every element of our culture. Though its primary function is religious, it is also important as a work of literature. It deals with themes such as the creation of the world, the concept of evil and the idea of the Promised Land.
VHS
Distributed by Felta Book Sales, Makati, Metro Manila.
Keywords: Bible as literature; Bible -- Criticism interpretation, etc